2015
DOI: 10.1002/2015ja021234
|View full text |Cite
|
Sign up to set email alerts
|

Source and seed populations for relativistic electrons: Their roles in radiation belt changes

Abstract: Strong enhancements of outer Van Allen belt electrons have been shown to have a clear dependence on solar wind speed and on the duration of southward interplanetary magnetic field. However, individual case study analyses also have demonstrated that many geomagnetic storms produce little in the way of outer belt enhancements and, in fact, may produce substantial losses of relativistic electrons. In this study, focused upon a key period in August–September 2014, we use GOES geostationary orbit electron flux data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
333
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 259 publications
(367 citation statements)
references
References 61 publications
32
333
1
1
Order By: Relevance
“…Jaynes et al . [] discussed that if any of the necessary populations (particle or wave) were not present in the radiation belts, the radiation belts would not be enhanced. Thus, following 50% of the substorm intervals that we studied, either the substorms did not produce the necessary wave population to accelerate the seed population or the seed population was not injected into the radiation belts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jaynes et al . [] discussed that if any of the necessary populations (particle or wave) were not present in the radiation belts, the radiation belts would not be enhanced. Thus, following 50% of the substorm intervals that we studied, either the substorms did not produce the necessary wave population to accelerate the seed population or the seed population was not injected into the radiation belts.…”
Section: Discussionmentioning
confidence: 99%
“…This seed population is anisotropic and unstable to the generation of whistler mode chorus waves [ Li et al ., , and references therein]. The seed population is subsequently locally accelerated through wave‐particle interactions with these whistler mode chorus waves [ Horne and Thorne , ; Summers et al ., ; Horne et al ., , ; Li et al ., ; Jaynes et al ., ] up to relativistic energies. Hence, substorms are thought to be the source of the electron seed population and the source of the wave growth that provides the acceleration of these particles to relativistic energies.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding how electrons are accelerated to ultrarelativistic energies in the radiation belts, several mechanisms have been considered to be potentially important. Although energetic electron injections during substorms or enhanced convection provide seed electrons (from tens of keV to hundreds of keV) [ Miyoshi et al ., ; Baker and Kanekal , ; Thorne , ; Boyd et al ., ; Dai et al ., ; Jaynes et al ., ], this process is unlikely to directly lead to the net electron acceleration up to multiple MeV. Inward radial diffusion caused by interaction with Ultra‐Low‐Frequency (ULF) waves can accelerate electrons to higher energies [ Hudson et al ., ; Mathie and Mann , ; Perry et al ., ; Ukhorskiy et al ., ], but this process alone is unlikely to account for the observed outer radiation belt electron dynamics which often exhibits growing radial peaks in electron phase space density (PSD) at ultrarelativistic energies in the heart of the radiation belts [ Green and Kivelson , ; Iles et al ., ; Chen et al ., ; Turner et al ., ; Reeves et al ., ; Thorne et al ., ; Kanekal et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent inner magnetospheric spacecraft missions such as THEMIS [Angelopoulos, 2008] and the Van Allen Probes [Mauk et al, 2012] have revealed the dynamic evolution of radiation belt particles and provided comprehensive information about acceleration, transport, and loss of energetic electrons [Baker et al, 2013[Baker et al, , 2014Reeves et al, 2013Reeves et al, , 2016Thorne et al, 2013b;Turner et al, 2014;Li et al, 2014Li et al, , 2016Jaynes et al, 2015;Boyd et al, 2016]. After the rapid electron flux enhancement during the geomagnetic storm, the long-term observation by the spacecraft generally indicates that the energetic electrons gradually diffuse radially accompanied by a persistent and slow loss process, before the interruption of a newly formed geomagnetic storm [Baker et al, 2014;Ma et al, 2015].…”
Section: Introductionmentioning
confidence: 99%